When Welfare Professionals Encounter Restructuring and Privatization: The Inside Story of the Probation Service of England and Wales. (December 2019) - Kirton, Gill; Guillaume, Cécile
This article utilizes a multi-method case study of the probation service of England and Wales to explore the perspectives of practitioners and their union on how restructuring/privatization affected the probation profession. Professionals perceived restructuring/privatization as ideologically and politically motivated, rather than evidence-based in relation to service goals. Against this context, the article outlines the probation union's organized resistance, but ultimately its inability to halt the reform. The findings highlight practitioners' concept of 'the death of probation' created by philosophical opposition to privatization, but also by the splitting of their profession and the resultant assault on professionalism. The study underlines the unique aspects of restructuring/privatization in the specific service domain, in particular those linked to working with a socially stigmatized client group, but it also has resonance for other public service professions facing the actuality or prospect of restructuring/privatization.